Kajian Hubungan antara Kekuatan Sambungan Paku dengan Diameter Paku dan Berat Jenis Kayu pada Beberapa Kayu Indonesia Study on Correlation between Nail Connection Strength and Both Nail Diameter and Specific Gravity on Several Indonesian Wood - Sucahyo Sadiyo; Agustina Suharti (Masyarakat Peneliti Kayu Indonesia, 2005)
On a strong, stiff, and stable wood construction for structural purposes, wood connection on several elements on its constituent is generally performed. On this construction, wood connection is a critical point. The strength of this connection is affected by the strength of 3 components, i.e. the connector, the wood, and the connection type. In a truss of structural construction, element of its constituent will receive compressive or tensile loads. In a case of connection, such load is called lateral resistance. In this study, the nail and several Indonesian wood species namely Sengon, Meranti, Kamper, and Bangkirai representing the low, moderate, and high specific gravity, were utilized. Effect of the nail diameter as a connector and wood specific gravity on wood connection has been investigated.The main objective of this research was to study the correlation between nail connection strength in two types of loading (lateral and withdrawal), and both nail diameter and wood specific gravity on several Indonesian wood.Based on this study there was a positive correlation between nail diameter and wood specific gravity on lateral or withdrawal resistance. Increasing both the nail diameter and wood specific gravity, resulted in increasing the wood connection strength. Correlation model for lateral and withdrawal resistances using P as the ultimate load, D as nail diameter, and G as wood specific gravity, respectively were P = 19.95 GD2.07 and P = 38.02 G1.42D